1994
DOI: 10.1136/bmj.309.6950.295
|View full text |Cite
|
Sign up to set email alerts
|

Risk of testicular cancer after vasectomy: cohort study of over 73 000 men

Abstract: Results-The overall pattern of cancer incidence in the study cohort was similar to that expected nationally. No increased incidence in testicular cancer was observed (70 cases; standardised morbidity ratio 1-01 (95% confidence interval 0 79 to 1.28)). The incidence during the first year of follow up was also close to that expected (nine cases; standardised morbidity ratio 0-80 (0.36 to 1.51)). The incidence of prostate cancer was not increased (165 cases; standardised morbidity ratio 0-98 (0.84 to 1.14)).Concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 26 publications
0
21
0
6
Order By: Relevance
“…Two large-scale studies (1 cohort study and 1 case-control study) found no association between vasectomy and testicular cancer. 120,121 A review of 8 articles 122 found only 1 study supportive of a positive association.…”
Section: Reproductive Healthmentioning
confidence: 99%
“…Two large-scale studies (1 cohort study and 1 case-control study) found no association between vasectomy and testicular cancer. 120,121 A review of 8 articles 122 found only 1 study supportive of a positive association.…”
Section: Reproductive Healthmentioning
confidence: 99%
“…There is no increased risk of testicular or prostate cancer associated with vasectomy [26,27]. Contrary to previously held notions, it is no longer recommended to inform patients about such potential risks; instead, vasectomy can be recommended as a safe form of male sterilization.…”
mentioning
confidence: 86%
“…Da sich, wie bereits oben diskutiert, das Menstruationsmuster durch die Sterilisation nicht wesentlich verändert [5] [29,30].…”
Section: Hysterektomierisikounclassified